The essential [compact disc] - Gardot, Melody (Decca, 2024)
"The Essential is a testament to Melody Gardot's enduring artistry. This collection spans 14 years of her career and includes 25 tracks that showcase the breadth of her musical abilities. Featuring selections from her six studio albums, remixes, live recordings and previously unreleased tracks, the album captures the essence of Gardot's talent. Highlights include her multilingual performances, emotive renditions of classics like Elton John's "Love Song," and live recordings that convey the raw honesty of her concerts. Each track offers a glimpse into the diverse emotional landscapes Gardot can traverse, making The Essential a rich and compelling portrait of an artist whose music speaks for itself"--Amazon.ca.